2015
DOI: 10.2118/169118-pa
|View full text |Cite
|
Sign up to set email alerts
|

Frontal-Stability Analysis of Surfactant Floods

Abstract: Recent surfactant-flooding experiments have shown that very-efficient oil recovery can be obtained without mobility control when the surfactant solution is injected at less than the critical velocity required for a gravity-stable displacement. The purpose of this study was to develop a method to predict the stability of surfactant floods at the reservoir scale on the basis of gravity-stable surfactant-flooding experiments at the laboratory scale. The scaleup process involves calculation of the appropriate aver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…On the other hand, conventional AF and SF can only improve the microscopic sweep efficiency. To examine the displacement efficiency of any enhanced oil recovery technique, particularly chemical flooding methods, a capillary desaturation curve (CDC) is constructed by conducting coreflooding tests at various flow rates [94,95]. A CDC usually reflects the pore structure, arrangement within the porous media, and fluid distribution inside these pores [96].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, conventional AF and SF can only improve the microscopic sweep efficiency. To examine the displacement efficiency of any enhanced oil recovery technique, particularly chemical flooding methods, a capillary desaturation curve (CDC) is constructed by conducting coreflooding tests at various flow rates [94,95]. A CDC usually reflects the pore structure, arrangement within the porous media, and fluid distribution inside these pores [96].…”
Section: Introductionmentioning
confidence: 99%
“…The simulations revealed that gravity stable surfactant floods can be very efficient at horizontal wells in reservoirs with a high vertical permeability [46]. These advantages become significant when the reservoir temperature is high and the use of polymer becomes increasingly difficult.…”
Section: Frontal-stability Analysis Of Surfactant Floodsmentioning
confidence: 99%
“…Recent surfactant-flooding experiments have shown that a very efficient oil recovery can be obtained without mobility control when the surfactant solution is injected at less than the critical velocity required for a gravity stable displacement [46]. A method has been developed to predict the stability of surfactant floods at the reservoir scale on the basis of gravity stable surfactant flooding experiments at the laboratory scale.…”
Section: Frontal-stability Analysis Of Surfactant Floodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The formation of a microemulsion phase and an oil bank was observed in displacement experiments. Microemulsion properties, especially viscosity, were found to be important for the determination of viscous stability of surfactant floods (Tavassoli et al 2014(Tavassoli et al , 2015. In an unstable displacement with an injection rate above the critical velocity, the formation of fingers was observed (Lu 2014;Tavassoli et al 2014).…”
mentioning
confidence: 99%